Assessment of Optical Detection Methods for Compact Biosensors - Efe, Onur; Yildirim, Tulay (IEEE, 2017)
There is an increasing demand in the society for an accurate cost sensitive compact biosensor. This is due to the fact that this kind of biosensor can slightly decrease the diagnosis period of diseases, which has major importance on the treatment period. Also it would not require facilities or expertise which is only available in hospital laboratories. Optical biosensors can offer very sensitive and accurate measurements. This paper includes working principles of different optical detection methodologies and evaluation of them for application on compact biosensors.
Keywords: compact biosensor; pathogen detection; optical biosensor; Engineering